The Effectiveness of E-Learning-Based Volleyball Service Video Media on Students Affected by Covid-19 at Faculty of Sports Science, Universitas Negeri Medan - Samsuddin Siregar; Indra Kasih; Herli Pardilla (Physical Education Theory and Methodology, 2022)
The study purpose. The online learning system, media, and resources used by lecturers to achieve volleyball learning goals are known to be not optimal. This study aimed to develop an e-learning video media that can be used by students as a learning resource to learn the material for upper serve, jump serve, and floating serve in volleyball games.